2021
DOI: 10.22460/pej.v5i1.1722
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Fifth Grade Students’ Number Sense and Their Mathematical Problem Solving

Abstract: This research was aimed to find the relationship between the fifth-grade students’ number sense and mathematical problem-solving. The participants of this study were 73 fifth grade students from a private Islamic school in Pekanbaru, Indonesia. This study applied a quantitative research method, namely a simple correlation. Instruments for measuring students’ number sense consist of 5 indicators; number concepts, multiple representations, effects of operations, equivalent expressions, and computing and counting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Previous research analyzed the effect of number sense on students' learning outcomes in Iran (Maryam et al, 2011) and on students' problem solving (Mutmainnah et al, 2021). Several studies show that there are significant differences when elementary school students do not understand master number sense.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research analyzed the effect of number sense on students' learning outcomes in Iran (Maryam et al, 2011) and on students' problem solving (Mutmainnah et al, 2021). Several studies show that there are significant differences when elementary school students do not understand master number sense.…”
Section: Introductionmentioning
confidence: 99%
“…Number sense ability will make students think flexibly so they can solve mathematical problems in various conditions and situations. However, some previous studies have shown that many students did not perform well in number sense (Mutmainnah, Putra, & Syahrilfuddin, 2021;Witri, Putra, & Nurhanida, 2015;Yang & Li, 2008). Students tend to struggle to solve number tasks with flexible strategies, such as using mental arithmetic.…”
Section: Introductionmentioning
confidence: 99%
“…One of the important roles of number sense is shown in problem-solving, namely providing skills to solve a problem (Mutmainnah et al, 2021). In this case, students will have the ability to understand the relationship between the core of the problem and the calculations that must be carried out, recognize, and use various ways and strategies to solve problems, use efficient and flexible number representations, estimate various possible answers to a problem, decide whether the answers obtained are following the problems at hand, and re-checking the results of the work and the answers generated.…”
Section: Introductionmentioning
confidence: 99%